UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN OPINI AUDITOR PADA AUDIT DELAY - Miradhi, Made Devi; Juliarsa, Gede (E-Jurnal Akuntansi, 2016)
The aim of this study was to determine the size of the company as a moderating influence profitability and the auditor's opinion on the audit delay. This study was performed on companies listed in Indonesia Stock Exchange in 2012-2014. Samples are taken as much as 72 manufacturing companies, with a purposive sampling method. Data used is secondary data media manufacturing companies in the form of financial statements. The data analysis technique used is Moderated Regression Analysis. Based on the analysis found that simultaneous independent variables affect audit delay in manufacturing companies. The size of the company strengthens the relationship between the profitability of the audit delay because research shows a significant value of 0.04. This is because companies are experiencing huge profits and have a lot of assets expand the lead auditor auditing financial statement so that the audit process will be longer
Keywords: Profitability, The Auditor' s Opinion, The Size Of The Company, The Audit Delay